Hydraulic and pneumatic power for production: how air and oil equipment can be applied to the manual and automatic operation of production machinery of all types withnumerous existing installations explained in step-by-step circuit analyses - 264707 Stewart, Harry L. (New York : Industrial Pr., 1970)
20